Peripheral Ossifying Fibroma: A Case Report - Sah, Barun Kumar; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Peripheral ossifying fibroma (POF) is a common solitary gingival growth thought to arise from the periodontal ligament. Though the etiology of POF remains unknown, some investigators consider it an inflammatory or reactive process, while others suggest it is a neoplastic process. Here, we present a case of POF in a 10-year-old boy, affecting the maxillary anterior gingiva along with its clinical, radiographic, histologic characteristics, differential diagnosis, treatment and one year follow-up.